Prediction equations for estimating carcass yields in Nellore and Nellore crossbred cattle - Luchiari Filho, Albino; Allen, Dell M. (Pesquisa Agropecuaria Brasileira, 2014)
Carcass data were used to develop equations for predicting weights of several cut-out yields for bulls from two experiments conducted at the Instituto de Zootecnia in São Paulo, Brazil. These data of 72 young bulls were obtained from 32 Nellore, 18 1/2 blood Marchigiana-Nellore, 12 1/2 blood Chianina-Nellore and 10 1/4 blood Marchigiana-Nellore. Equation 1, used to predict weight of trimmed total carcass cuts (Y = -6.8074 + 0.8021 (chilled carcass weight in kilograms - 3.1021 (kidney and pelvic fat percentage)+ 0.2743 (fat thickness in millimiters)), would seem to be the most useful, since it utilizes three easily obtainable variables and is highly accurate (R2 = 0.96). Chilled carcass weight was the independent variable with the greatest contribution in all prediction equations. All the models included chilled carcass weight and kidney and pelvic fat percentage as independent variables.